The Students' Perception of Learning English as Foreign Language in Pandemic Covid 19 - Rahmawaty Mamu; Sri Ayu Musa; Elsje Louise Sambouw (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
This research aimed to find out the student's perception of learning English during the pandemic covid 19. This research used a qualitative descriptive method. In order to answer the research question, the researcher collected the data from 13 open-ended statements interviewed by students at SMP Negeri 2 Satap Dungaliyo. The researcher used data reduction, data display, and conclusion to analyze the data. And the result of this research is that English in the pandemic covid 19 has various student answers. There are advantages and also disadvantages to the implementation of online classes in the pandemic era. It depends on the students themselves; each of them has their own perception regarding learning English during the pandemic covid 19, and also their own experienced they faced in their environment. These statements were gained by the result of the research conducted in SMP Negeri 2 Satap Dungaliyo.The coronavirus outbreak that has hit this country poses a challenge for the community and educational institutions, so to anticipate the spread of the virus, the Ministry of Education has set the learning system to be carried out with an online system.